2018
DOI: 10.1007/s13361-018-2009-8
|View full text |Cite|
|
Sign up to set email alerts
|

Measurements of Atmospheric Proteinaceous Aerosol in the Arctic Using a Selective UHPLC/ESI-MS/MS Strategy

Abstract: In this article, an analytical methodology to investigate the proteinaceous content in atmospheric size-resolved aerosols collected at the Zeppelin observatory (79 °N, 12 °E) at Ny Ålesund, Svalbard, from September to December 2015, is proposed. Quantitative determination was performed after acidic hydrolysis using ultrahigh-performance liquid chromatography in reversed-phase mode coupled to electrospray ionization tandem mass spectrometry. Chromatographic separation, as well as specificity in the identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…Amino acids and fatty acids have previously been observed in the SML of open leads in the summer high Arctic 61,62 and in bulk ambient aerosols during spring–summer in the Canadian Arctic 60,63 and during spring–fall at Svalbard. 64,65 Notably, all SSA particles containing amino acids also contained saccharides, and most particles (75%, by number) containing one short-chain fatty acid also contained a saccharide signature. Only 33% of particles matching saccharides did not contain any other organic type.…”
Section: Resultsmentioning
confidence: 99%
“…Amino acids and fatty acids have previously been observed in the SML of open leads in the summer high Arctic 61,62 and in bulk ambient aerosols during spring–summer in the Canadian Arctic 60,63 and during spring–fall at Svalbard. 64,65 Notably, all SSA particles containing amino acids also contained saccharides, and most particles (75%, by number) containing one short-chain fatty acid also contained a saccharide signature. Only 33% of particles matching saccharides did not contain any other organic type.…”
Section: Resultsmentioning
confidence: 99%
“…Concerning abiotic transformation (photo-transformation and radical chemistry) in atmospheric waters, some studies determined kinetic rate constants (k) of AAs with radicals (e.g., OH) (Scholes et al, 1965;Motohashi and Saito, 1993;Prütz and Vogel, 1976), singlet oxygen ( 1 O 2 ) (Kraljić and Sharpatyi, 1978;Matheson and Lee, 1979;McGregor and Anastasio, 2001;Michaeli and Feitelson, 1994;Miskoski and García, 1993;McGregor and Anastasio, 2001), or ozone (O 3 ) (Ignatenko and Cherenkevich, 1985;Pryor et al, 1984). Based on such kinetic data, some studies have reported the time of life of amino acids in fog (McGregor and Anastasio, 2001) or in cloud water (Triesch et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In general, previous studies have shown that amino acids in aerosol particles can have both natural and anthropogenic sources. Having been detected in volcanic emissions (Scalabrin et al, 2012) and during biomass burning events (Chan et al, 2005;Feltracco et al, 2019), amino acids can be produced by plants, pollens, fungi, bacterial spores and algae (Milne and Zika, 1993;Zhang and Anastasio, 2003;Matos et al, 2016). Nevertheless, they are useful indicators for aerosol particle age and origin (Barbaro et al, 2011;Matsumoto and Uematsu, 2005;Scalabrin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although the study and characterization of amino acids are of paramount importance for atmospheric scientists, the true role and the fate of amino acids in the atmosphere are still poorly understood (Matos et al, 2016). Despite several studies of FAAs also conducted in the marine environment, there is still a huge uncertainty as to the question of whether FAAs are of marine origin or not.…”
Section: Introductionmentioning
confidence: 99%